Heat Pump Installations for Large Non-Domestic Buildings : CIBSE AM17: 2022 - Bird, Joshua (The Chartered Institution of Building Services Engineers (CIBSE), 2022)
Supplies best practice guidance to assist in the provision of high quality design, installation, commissioning, operation and maintenance of large heat pump systems. Discusses large heat pump installations with a thermal output exceeding 45 kW, providing space heating, cooling, domestic hot water and process heat. Looks to increase awareness of the common issues encountered when supplying effective heat pump systems in larger buildings.
Keywords: Heat pumps -- Thermodynamics.; elektronické knihy; electronic books